The deterritorialized or multiterritorial landscape. A point of view from the work “Out of place” by Edward Said - Ramón Margueliche, Juan Cruz (2020)
Out of Place was published for the first time in 1999 and based on its content, it could have been part of the prologue of “Orientalism” (1978), one of Said’s masterpieces. In Out of Place, Said materialises and brings to life his postulates written in Orientalism, but he does so from an autobiographical-I place. It is through his different journeys: travels, moves and exiles (voluntarily or not) that the author displays as true transcultural itineraries (Clifford, 1999). This way of life allowed him not only to constitute himself as a subject (to transit age passages), but also as a writer-resident of the places that were always in tension between complex and hybrid situations that were looking to (de) legitimise himself. It could be pointed out that Said knew how to live through the permanent mobility, being a subject in a constant search of auto identification. We will work this piece through the concepts of landscapes and deterritorialization in order to understand Said’s life and its cultural configurations in a place that no longer responded to the traditional structure of representation that the Nation-Estate (still) imposes.